2014
DOI: 10.1373/clinchem.2013.207951
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Fetal Cell-Free DNA Fractions Differ in Autosomal Aneuploidies and Monosomy X

Abstract: BACKGROUND:Noninvasive prenatal testing based on massively parallel sequencing (MPS) of cell-free DNA in maternal plasma has become rapidly integrated into clinical practice for detecting fetal chromosomal aneuploidy. We directly determined the fetal fraction (FF) from results obtained with MPS tag counting and examined the relationships of FF to such biological parameters as fetal karyotype and maternal demographics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
155
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(184 citation statements)
references
References 20 publications
20
155
1
8
Order By: Relevance
“…Although the total fetal fraction of twin pregnancies might be higher than that of singletons10, the individual contribution from each twin is generally lower than that of a singleton8, 9; however, there may be exceptions. In our study, the average combined fetal fraction of both twins (16.1%) was higher than determined previously for singletons over similar gestational‐age ranges (12.6%; P  = 0.001)21, and higher still than the average fetal fraction for a single twin (7.8%; P  < 0.0001), consistent with the previously mentioned studies. Rava et al .…”
Section: Discussionsupporting
confidence: 92%
“…Although the total fetal fraction of twin pregnancies might be higher than that of singletons10, the individual contribution from each twin is generally lower than that of a singleton8, 9; however, there may be exceptions. In our study, the average combined fetal fraction of both twins (16.1%) was higher than determined previously for singletons over similar gestational‐age ranges (12.6%; P  = 0.001)21, and higher still than the average fetal fraction for a single twin (7.8%; P  < 0.0001), consistent with the previously mentioned studies. Rava et al .…”
Section: Discussionsupporting
confidence: 92%
“…20 However, fetal fraction is lower when the fetus has trisomy 18, 13, or monosomy X, although it is still above the threshold fetal fraction of 4% that is needed to obtain a result. 21 Therefore, we feel it is a coincidence, rather than an intrinsic problem of the test, that all our "unclassified" results occurred in the second and third trimester. In three morbidly obese patients, the NIPT yielded no result, as there was an insufficient fetal fraction for analysis.…”
Section: Discussionmentioning
confidence: 86%
“…24 Others showed that a fetal fraction of DNA in Down syndrome cases is often the same or higher when compared to pregnancies with euploid fetuses. 46,47 Since the introduction of NIPS into clinical practice, fetal fraction has not been uniformly reported by laboratories. The described relationship between low fetal fraction and increased risk of aneuploidy adds to the importance of reporting the reason for a no-call and of indicating in the report whether a low fetal fraction was identified.…”
Section: How Are No-calls Avoided Interpreted and Managed? Fetal Frmentioning
confidence: 99%